La recherche de la salinité des eaux de mer des deux sites Sidi Medjdoub et Sablettes par usage des différentes méthodes physico-chimiques - Belahouel, Hind (My University, 2022)
The sea is a major economic resource for coastal regions: fishing (fisheries), tourism, transport, logistics (port activity)…… The pollution of these coastal marine areas is due to the modification of the physical, chemical or biological properties or any discharge of liquid, gaseous or solid matter into the sea waters. To detect the chemical pollution of these waters, we study the physico-chemical parameters such as temperature, pH, conductivity, chloride dosage, dissolved oxygen, etc. Our objective is to study a pollution index indicating the rate of salts or salinity of the sea water of the two sites Sidi Medjdoub and Sablettes by using different physico-chemical methods such as the dosage of chlorides, the determination of conductivity , the study of salinity, the search for the total mineralization rate (TDS) and the search for the dry residue. The results show that the measurements of these physico-chemical parameters of seawater are within the norm.
Keywords: salinity; physicochemical parameters; seawater; pollution; Sablettes; Sidi Medjdoub